The Long-Term Presence of SARS-CoV-2 on Cold-Chain Food Packaging Surfaces Indicates a New COVID-19 Winter Outbreak: A Mini Review - Chi, Yuhua; Wang, Qingxiu; Chen, Guosheng; Zheng, Shiliang (Frontiers in Public Health, 2021)
Severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) is a highly infectious virus that is transmitted primarily by droplet or close contact. 2020 saw a full-blown global outbreak of COVID-19, resulting in an unprecedented global burden of disease, healthcare costs, and economic impact. Recently, SARS-CoV-2 has been detected on the outer packaging of imported cold chain items in China and has led to coronavirus transmission events. This issue has caused concern and worry. We analysed the coronavirus characteristics and transmission, factors affecting its transmission and survival in different places and environments, especially the characteristics of low temperature and object surfaces. It was found that SARS-CoV-2 survived for a long time on the surface of cold and moist objects in the cold chain for more than 3 weeks, potentially causing the transmission of COVID-19. We believe that the low-temperature environment in winter may accelerate the spread of the outbreak and a new outbreak may occur. Overall, our view of SARS-CoV-2's susceptibility to disease transmission by low winter temperatures is critical for predicting winter pandemics, thus allowing us to take appropriate approaches to contain them in advance.